House of spies - Silva, Daniel, 1960- (New York : Harper, an imprint of HarperCollinsPublishers, 2017)
Four months after the deadliest attack on the American homeland since 9/11, terrorists leave a trail of carnage through London's glittering West End. The attack is a brilliant feat of planning and secrecy, but with one loose thread. The thread leads Gabriel Allon and his team of operatives to the south of France and to the gilded doorstep of Jean-Luc Martel and Olivia Watson.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; France -- Fiction; Thrillers (Fiction)